A new approach to optimize variable axial composite shells: A metaheuristic procedure using the finite element method. (February 2023) - Santana, Pedro Bührer; Gomes, Herbert Martins; de Almeida, Felipe Schaedler; Tita, Volnei
Abstract: A strategy for the design of optimum fiber pattern of constant thickness variable-stiffness laminated composite plates and shells is presented and evaluated. The optimization framework employs finite element analysis and the particle swarm optimization (PSO) algorithm, but the main contribution lies in the method proposed for the parametric description of the fiber orientation. Scalar values assigned to control points distributed in advance on the structure are taken as the design variables. These values are interpolated at the nodes of the finite element mesh using a radial basis function (RBF). The fiber orientation on the surface of the structure is continuously defined by the gradient of the scalar field obtained by the interpolation of the nodal values using the finite element shape functions. This approach is applicable to flat and curved structures, ensuring fiber continuity and demanding less design variables than element-wise fiber angle optimization. The effectiveness of the proposed strategy is evaluated by the optimization of a flat plate, a shallow shell with a hole and a pressure vessel. Highlights: A new approach to parameterize the fiber angles in shell-like structures using FE shape functions. A strategy to VA composites optimization considering stress, natural frequencies and buckling loads. A framework to generate continuous curvilinear fiber patterns for 3D shell composite structures.